The Influence of Morale and Internal Locus of Control Toward Organizational Commitment on Civil Servants at Transportation Department of Pontianak City - Suci Rahmadiah; Devi Yasmin; Irfan Mahdi (UM Purwokerto Press, 2024)
This research aims to determine the influence of morale and internal locus of control on the organizational commitment of civil servants at Transportation Department of Pontianak City. This research employs an associative research method. The population in this study consists all civil servants at Transportation Department of Pontianak City. Totaling 62 civil servants working at Transportation Department of Pontianak City. The sampling technique used in this research is total sampling. The data analysis tools used in this study are multiple linear regression analysis, multiple correlation coefficient (R), coefficient of determination (R2), simultaneous test (F test), and partial test (t test). The research results indicate that the multiple linear regression equation model is: Y = 0.995 + 0.418X1 + 0.312X2. The correlation coefficient value shows an R value of 0.581, indicating that morale (X1) and internal locus of control (X2) have a significant correlation with organizational commitment (Y). The coefficient of determination value, denoted as R2, is 0.337, which means that morale and internal locus of control collectively influence organizational commitment by 33.7%, while the remaining 66.3% is influenced by other factors not examined in this study. The simultaneous test results (F-test) indicate a significant influence of both morale and internal locus of control on organizational commitment. The partial test results (t-test) show that there is a significant influence of morale on organizational commitment and a significant influence of internal locus of control on organizational commitment.